Technical review on vinegar fermentation process and physiochemical properties of vinegar product based on Shariah and scientific perspectives - Jamaludin, Mohd Aizat; Md. Amin, Nur Alifah; Othman, Rashidi; Ahmad Fadzillah, Nurrulhidayah; Muflih, Betania Kartika (Springer Nature, 2018)
Vinegar, as its name indicates, was made from wine at a remote period. Vinegar is essentially a dilute solution of acetic acid that was created through the process of fermentation, containing salts and extracted matter. It is also one of the most widespread and common acetic acid-diluted solution product in the world. All the additional substances, exact nature and quantity of which depend upon the material used, give the product its distinctive quality. Sugar is the basic ingredient in vinegar production. Any watery solution of a fermentable sugar may be transformed into vinegar under favorable conditions. Many fruits juices are well suited for this purpose as they contain sugar in the proper proportion and other necessary or desirable substances. The commercial vinegar production is performed with fast or slow fermentation processes. During the fast fermentation method, the liquid of damaged fruits is oxygenated and the fermentation is rapidly carried out by introducing the bacteria starter culture. Meanwhile, the slow method of producing vinegar is generally used for the production of traditional wine vinegars and the process may take weeks or months. It is shown that a nontoxic slime that is known as the mother of vinegar comprises of yeast and acetic acid bacteria on the surface. The final vinegar products possess unique functions, consisting of various compounds formed during the fermentation process. The quality of vinegar is determined by many factors, especially by the raw materials and microbial diversity involved in vinegar fermentation . Therefore, the physiochemical properties of vinegar are determined by many factors such as the types of materials involved in their production (cider, wine, and honey), types of fermentation methods and their organoleptic properties. Besides that, Food and Agricultural Organization/World Health Organization also has defined vinegar as a liquid fit for human consumption exclusively produced from an agricultural raw material, containing starch and sugars by a double alcoholic and acetic acid fermentation process. That is why vinegar is considered as a traditional ingredient in food production and is one of the popular food additives all around the world.